CERITA RAKYAT BALI (SATUA ) SEBAGAI MEDIA PEMBELAJARAN KEKRITISAN PENALARAN ANAK USIA SEKOLAH DASAR DAN PENDIDIKAN KARAKTER - I Nyoman Sadwika; I Nyoman Astawan (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
Good entertainment which is packaged in the form of reading satua (stories) for children is very supportive and good for children’s characters. Satua has a good value form local genius from a region, this value very relevant and give a good impact for child development escepecially primary student. The aim of this paper is for developing satua as a critical learning media for primary student. Satua is one of the effective media for building children's character. Satua as part of the literature recognizes that it has a positive contribution to the development of children's personality, if one is given the involvement of instilling, fostering, developing, and even preserving the values ​​of character education.